2014
DOI: 10.1007/s10900-014-9941-8
|View full text |Cite
|
Sign up to set email alerts
|

Proyecto MercadoFRESCO: A Multi-level, Community-Engaged Corner Store Intervention in East Los Angeles and Boyle Heights

Abstract: Urban food swamps are typically situated in low-income, minority communities and contribute to overweight and obesity. Changing the food landscape in low income and underserved communities is one strategy to combat the negative health consequences associated with the lack of access to healthy food resources and an abundance of unhealthy food venues. In this paper, we describe Proyecto MercadoFRESCO (Fresh Market Project), a corner store intervention project in East Los Angeles and Boyle Heights in California t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 13 publications
1
78
0
Order By: Relevance
“…Beyond availability and marketing, using demand-driven and community engagement strategies have been recognized as key to successful interventions [47, 72]. More work is needed to create reasonable policies and programmatic approaches that reach stores that have not historically participated in intensive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond availability and marketing, using demand-driven and community engagement strategies have been recognized as key to successful interventions [47, 72]. More work is needed to create reasonable policies and programmatic approaches that reach stores that have not historically participated in intensive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of the study has been described in detail elsewhere. 8 In brief, to evaluate the intervention we conducted a community household survey in neighborhoods surrounding corner stores in East Los Angeles and Boyle Heights. There were a total of eight sample sites situated around these corner stores, grouped into four dyads, each with a treatment and control arm.…”
Section: Methodsmentioning
confidence: 99%
“…More information on these activities is described in Ortega and collegues. 8 Although VELA was a valuable partner, the study was conceived of and designed by academic researchers, and thus our approach was a community-engaged one rather than a community-based participatory research one.…”
Section: Methodsmentioning
confidence: 99%
“…Several of these studies reported results from monitoring the process implemented by the corner stores and consumer perceptions of change in the store environment [72, 88]. Strategies included increased stocking of healthy foods such as fresh fruits and vegetables, beans, lean meats, whole wheat bread and low-fat dairy, increased promotion of healthy items, decreased promotion or moving of less healthy items such as sugar-sweetened beverages, price discounts for healthy foods, grants for refrigeration units, training of managers/owners on how to stock, market healthy foods, social media, community, flyers, and signage [74, 84, 85, 8789]. Four studies only reported preliminary results and did not include information on individual/consumer behavior [72, 84, 85, 89].…”
Section: Food Retail Environment Interventionsmentioning
confidence: 99%